Morphological Analysis of Healthy Aortic Arch. (May 2017) - Boufi, M.; Guivier-Curien, C.; Loundou, A.D.; Deplano, V.; Boiron, O.; Chaumoitre, K.; Gariboldi, V.; Alimi, Y.S.
Abstract : Objective/Background: This study aimed to describe an arch morphology protocol in a healthy population, and to assess the impact of age and sex. Methods: A retrospective morphology evaluation was conducted in a population with no personal history of thoracic aorta surgery or pathology, through computed tomography (CT) imaging analysis, using a standardised protocol. Based on centreline three dimensional coordinates, a single investigator calculated a series of parameters in the arch zones and in the total arch, using Matlab scripts. These were categorized as: (i) morphometric data: diameter, length and aortic angle of each zone, total arch angle, and length; (ii) geometric data: tortuosity index (TI), arch width, assimilated curvature radius (CRi ), and attachment zone angles. Student or Mann–Whitney tests were used to compare parameter means. Their variability with age and sex was assessed through univariate and multivariate regression analysis. Results: CT images from 123 subjects (mean ± SD age 53 ± 19 years) were reviewed. Significant correlation between age and morphology was found. The aorta expanded homogeneously and stretched heterogeneously with age because of posterior arch elongation. TI decrease, CRi, and attachment zone angle increase were also observed with aging. Age remained significantly associated with these morphological parameters, independently of body surface area and hypertension. Sex also affected morphology: longer total arch length and higher CRarch in men; lower zone 3 attachment angle in women Conclusion: Using mathematical algorithms, and with a view to improving endovascular arch treatment, this study provides a standardised arch morphology protocol and objectively identifies both age related evolution and sex related variation in the different zones.